Sovereign Debt and the Financial Crisis : Will This Time Be Different? - Primo Braga, Carlos A. (World Bank, 2012)
The financial crisis of 2008 has rekindled interest in sovereign debt crises among policy makers and scholars. History shows that lending booms typically end in busts, with the beneficiaries of debt in the upswing often forced to default or reschedule their debts in the downswing (Sturzenegger and Zettelmeyer 2006). The impact of the first financial crisis of the 21st century on capital flows to developing countries and the signs of stress in debt markets of several European countries in the first half of 2010 raise the inevitable question, Are author about to witness a new generation of sovereign debt crises? This book addresses this question. It adopts an integrated approach by drawing on both theoretical research and experience from professionals involved in technical assistance in this area. It documents recent improvements in macroeconomic policies and debt management practices, which to a large extent explain the resilience of developing and emerging economies, and identifies challenges ahead and areas that require special attention from policy makers.